Análisis in silico de los genes del operón virB de Brucella canis aisladas de caninos de criaderos en el área metropolitana del Valle de Aburrá (Antioquia, Colombia) (2013)
ABSTRACT: Canine brucellosis is a zoonotic disease caused by Brucella canis. The establishment of intracellular replicative niches of B. canis is mediated by proteins secreted by the type IV secretion system, which is encoded by the virB operon. The characterization of such genes has been conducted in other species of the genus, but few in B. canis. We report the evaluation of the nucleotide sequences of the virB genes in seven isolates obtained from kennels in the metropolitan area of Aburrá Valley in Antioquia, Colombia. Sequences were obtained from a previous study and were compared with publicly available sequences from other Brucella strains using multiple alignment analysis and phylogenetic methods. All sequences of the native isolates tested were different from one another, even those belonging to the same kennel, which may indicate the presence of multiple bacterial clones circulating in the studied area or variations in the bacteria intra host. Key words: Brucella canis, canine brucellosis, virulence factors, bacterial genes, zoonosis.